Implications on The Position of A Notary for Notaries Who Serve as Legislative Members - Yap, Jacqueline; Nurdin, Aad Rusyad (Faculty of Law, Universitas Pekalongan, 2024)
Notary as a public official, is an honorary position that is given the trust to make authentic deeds as written evidence, as mandated by laws and regulations. As part of the people, it is possible for a notary to take part in political practices by running for the legislature. The Notary Position Law and the General Election Law prohibit the practice of dual positions. Therefore, notaries who are appointed as legislative members are required to take leave in accordance with the provisions of the Notary Position Law. However, the implementation of the position carried out by the substitute notary can be indicated as a disguised dual position. Thus, the idea of entrusting the notarial appointment decree to the Regional Supervisory Council during his/her tenure as a legislator was proposed.